Temporal Dynamics of Serum Perforin and Granzyme during the Acute Phase of SARS-CoV-2 Infection - MD Tazikur Rahman; Sukhyun Ryu; Chiara Achangwa; Joo-Hee Hwang; Jeong-Hwan Hwang; Chang-Seop Lee (Vaccines, 2023)
Background: As many SARS-CoV-2 infections are asymptomatic, it could be useful to be able to determine how much time has passed since infection. We explored the changes in the temporal levels of T cell-related proteins (including perforin and granzymes) in the sera of patients with SARS-CoV-2 infection using a commercially available assay. Methods: This study enrolled 36 patients infected with SARS-CoV-2 and 20 healthy control participants. Blood samples were collected at three different times based on the number of days since symptom onset (early phase: 1–5 days, mid-phase: 6–10 days, late phase: 11–18 days). We assessed the temporal changes in the serum levels of perforin and granzymes in patients with SARS-CoV-2 infection by comparing the results with those obtained in the healthy control group. Results: We identified a significantly low level of perforin in the early phase of SARS-CoV-2 infection (p < 0.01), which was restored to normal during the mid- and late phases of the infection. However, there was no difference in the temporal change in the level of granzymes in SARS-CoV-2-infected patients compared to the healthy control group. Conclusions: This finding suggests that SARS-CoV-2 infection paralyzed the perforin expression in the early period immediately after infection. Thus, serum perforin is a potential marker for identifying the acute phase of SARS-CoV-2 infection.